Романы. Повесть. Рассказы. Эссе: 1946-1954 / [комментарии Г. Ю. Бергельсона] - Белль Генрих (1989)
Экземпляры: ЦБ (20250116) / Инвентарный номер: 22882 / Цена: 6.00 / Сис.шифр: И(нем) / Авт.знак: Б 43 / ГРНТИ: 17.82.82 / ББК: 84(4Нем)